Effect of number of seedlings hill-1 on the yield and yield contributing characters of short duration Aman rice cultivars - Islam, T; Salam, MA (Progressive Agriculture, 2018)
The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University (BAU), Mymensingh during the period from July to October 2016 to study the effect of age of seedling on the yield and yield contributing characters of short duration Aman rice cultivars. The study consisted two factor A: Variety- three- i) BINA dhan7 (V1), (ii) BRRI dhan56 (V2) and (iii) BRRI dhan62 (V3); and factor B: Number of seedlings hill-1- (i) Single seedling hill-1 (S1), (ii) Two seedlings hill-1 (S2) and (iii) Three seedlings hill-1 (S3). The experiment was laid out in a randomized complete block design with three replications. The highest grain yield was obtained from the cultivar BINA dhan7 which was statistically identical with BRRI dhan56 and this was the consequences of higher number of total and effective tillers hiil-1 and highest number of grains panicle-1. Grain yield was not significantly affected by the number of seedlings hill-1 but numerically the highest grain yield was recorded from single seedling hill-1. From the interaction it is observed that grain yield was not significantly affected by the interaction of cultivar and number of seedlings hill-1. But numerically the highest grain yield was recorded from the interaction of BRRI dhan56 × single seedling hill-1. From the economic analysis it is observed that the highest BCR (1.64) was recorded from single seedling hill-1 in BRRI dhan56 which was close to single seedling hill-1 in BINA dhan7 and the lowest BCR (103) was obtained from two seedlings hill-1 in BRRI dhan62. From the results of the study it may be concluded that BRRI dhan56 with single seedling hill-1 might be cultivated in AEZ-9 for obtaining higher yield and higher economic return in Aman season. Progressive Agriculture 28 (4): 279-286, 2017